ABCA3 and LZTFL1 Polymorphisms and Risk of COVID-19 in the Czech Population - Hubacek, Jaroslav A; Philipp, Tom; Adámková, Věra; Májek, Ondřej; Dušek, Ladislav (Physiological research, 2023)
SARS-CoV-2 infection, which causes the respiratory disease COVID-19, has spread rapidly from Wuhan, China, since 2019, causing nearly 7 million deaths worldwide in three years. In addition to clinical risk factors such as diabetes, hypertension, and obesity, genetic variability is an important predictor of disease severity and susceptibility. We analyzed common polymorphisms within the LZTFL1 (rs11385942) and ABCA3 (rs13332514) genes in 519 SARS-CoV-2-positive subjects (164 asymptomatic, 246 symptomatic, and 109 hospitalized COVID-19 survivors) and a population-based control group (N?=?2,592; COVID-19 status unknown). Rare ABCA3 AA homozygotes (but not A allele carriers) may be at a significantly increased risk of SARS-CoV-2 infection [P?=?0.003; OR (95 % CI); 3.66 (1.47-9.15)]. We also observed a borderline significant difference in the genotype distribution of the LZTFL1 rs11385942 polymorphism (P?=?0.04) between the population sample and SARS-CoV-2-positive subjects. In agreement with previous studies, a nonsignificantly higher frequency of minor allele carriers was detected among hospitalized COVID-19 subjects. We conclude that a common polymorphism in the ABCA3 gene may be a significant predictor of susceptibility to SARS-CoV-2 infection.
Keywords: ATP-Binding Cassette Transporters; Česká republika; lidé; Genotype; ABC transportéry; SARS-CoV-2; genotyp; Polymorphism, Genetic; Transcription Factors; transkripční faktory; Czech Republic; COVID-19; polymorfismus genetický; Humans